Patient participation in multidisciplinary tumor conferences in breast and gynecological cancer care: How patient‐centered is the communication?. Issue 9 (16th July 2022) - Schellenberger, Barbara; Heuser, Christian; Diekmann, Annika; Ansmann, Lena; Krüger, Emily; Schreiber, Leonie; Geiser, Franziska; Karger, André; Schmidt‐Wolf, Ingo G. H.; Milz, Katrin; Peisker, Uwe; Ernstmann, Nicole
Abstract: Objective: Patients' participation is part of patient‐centeredness, but it is so far unclear whether providers in multidisciplinary tumor conferences (MTCs) with patient participation communicate in a patient‐centered way. Our aim is to explore (a) to what extent providers ask questions to breast and gynecological cancer patients during case discussion in MTCs, (b) how providers respond to patients' expressions of emotions during case discussions, and (c) which patient‐ and context‐related characteristics and responses are associated with patients' trust in the treatment team after the case discussion. Methods: This observational study included survey data and audio recordings of MTCs with patient participation at three breast and gynecological cancer centers. Providers' questions to patients and responses to patients' emotional expressions were coded using the Verona Coding Definitions of Emotional Sequences. The response can be explicitly or non‐explicitly related to the emotion and space‐reducing or space‐providing. Multiple linear regression analysis was used to determine associations between providers' responses, patient‐ and context‐related characteristics, and patients' trust in the treatment team after the case discussion. Results: We analyzed 82 case discussions (77 breast, 5 breast and gynecological cancer patients). Providers asked a total of 646 questions, of which 86% were polar (yes/no). Providers gave 303 responses to a total of 230 emotional expressions by patients. Non‐explicit responses were associated with more trust when they were space‐providing, but with less trust when space‐reducing. Conclusions: The frequency of providers' closed questions and space‐reducing responses to emotions shows that patient‐centered communication rarely takes place in MTCs with patient participation.